Application of ground penetrating radar for evaluating foundation structure condition after earthquake - Apdeni, Risma; Citra, Zel; Rifwan, Fitra; Putri, Prima Yane; Sandra, Nevy; Malinda, Yosie; Wibowo, Paksi Dwiyanto; Ashadi, Reza Ferial; Melinda, Annisa Prita (Universitas Negeri Padang, 2024)
At the time of seismic activity, the failure of the foundation structure will lead to building damage. When the West Pasaman 2022 earthquake occurred, PT. XYZ is constructing a feed mill tower. Since strong earthquake shocks were felt at the project location, foundation structure evaluation is needed to ensure the safety of the building. Ground Penetrating Radar (GPR) is a tool that is widely used to detect subsurface conditions. This study used GPR as a non-destructive testing technique to evaluate the condition of the foundation structure. The building evaluated is a high-rise steel building, using spun pile foundation. GPR test was carried out in specified lanes, with measurement tracks set at 10 lanes. Any cracks or fractures on the foundation will be indicated by the interruption of waves at the point of the crack or fracture. The GPR test results from readings of electromagnetic wave propagation showed that waves can reach the end of each foundation tested, ranging from 17.10 m to 17.82 m deep. It means that there are no cracks or fractures found on the slab, pile cap, or foundation. Analysis results showed that all slabs and pile caps thicknesses and the detected foundation piles depths are in accordance with the foundation design, which means that the foundations are still in good condition.